(untitled) (Journal of Applied Learning and Teaching, 2024)
Professor Rose Luckin, a pioneer in the integration of artificial intelligence with education, holds the position of Professor of Learner Centred Design at the UCL Knowledge Lab, University College London. Her trailblazing research has profoundly deepened our understanding of AI in education (AIEd). Rose Luckin has authored over 50 peer-reviewed articles and key works, including “Machine learning and human intelligence: The future of education for the 21st century.” As the Director of EDUCATE, she merges academic insights with ed-tech industry innovation. She is the co-founder of the Institute for Ethical AI in Education. In our interview, Rose Luckin shares her educational awakening and her personal journey into AIEd, addressing gender bias and the unique challenges faced by women in the AI field. She delves into the ethical dimensions of AI deployment in educational settings, underscoring the Institute for Ethical AI in Education’s pivotal role in fostering ethical standards. Professor Luckin advocates for AI’s potential to bolster learner-centred methodologies and stresses the critical importance of forging robust partnerships between educators and technology developers. She evaluates the impact of generative AI on assessment, learning and teaching within K-12 and higher education. She provides insights into AI’s evolving role in education and the imperative of lifelong learning. Emphasising a collaborative ethos among educators, researchers, and developers, Professor Luckin argues for AI’s integration into education within strategically crafted ethics and governance frameworks. Our interview sheds light on AIEd’s current landscape, highlighting the critical need for ongoing research and collaborative efforts in navigating its considerable dangers while seizing opportunities.